IMPLEMENTASI PERATURAN MENTERI PENDIDIKAN DAN KEBUDAYAAN REPUBLIK INDONESIA NOMOR 28 TAHUN 2016 TENTANG SISTEM PENJAMINAN MUTU PENDIDIKAN DASAR DAN MENENGAH DI SMK NEGERI 1 SAMPANG - Hidayantari Erlyna (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2018)
Implementation is important to do something, giving a practical result to something. Successful implementation by two major variables, namely policy content (policy implementation) and implementation implementation. The Quality Assurance System of Primary and Secondary Education is a unity consisting of organizations, policies and integrated processes that regulate all activities to promote the most systematic, planned and sustainable quality of basic and water education. The Internal Quality Assurance System is an integral part of the policy to ensure the quality of education conducted by each unit of primary education and educational unit to translate quality education that meets or standards of the National Education Standards. The purpose of this study describes and apply the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 28 of 2016 on the Quality Assurance System of Primary and Secondary Education in SMK Negeri 1 Sampang and moderate speed. The type of this research is descriptive qualitative research using purposive sampling approach and data technique in this qualitative descriptive study using triangulation or combination. The result of this study is one of the requirements that must be considered by SMK Negeri 1 Sampang on the Education Assessment Standards, from the SPMI Cycle in SMK Negeri 1 Sampang, it is determined that the Quality of Education Units namely the Academic Information System (SIA) and CBT program and the implementation will succeed all interested parties.